Sports tourism as a new form of tourist activity - terminology and history of the concept - Bartłomiej Łuć (Jan Długosz University in Częstochowa, 2023)
This article deals with the broadly understood concept of sports tourism. Although this term has been used for a relatively long time, it was not until the 1970s that research on the concept and all kinds of considerations began. The complex nature of the phenomenon and the research being carried out all the time result in many doubts regarding this concept. The development of research and reflection on this concept is becoming more and more apparent every year. The increase in the number of publications relating directly to this topic is also strongly noticeable. In this article, an attempt has been made to order and systematize scientific publications and re- search results that have been developed so far. The article has been prepared on the basis of a search and analysis of literature sources related to both sports tourism and the geography of tourism, or concepts related to sport. Both foreign literature and Polish literature sources were taken into account. The aforementioned literature review was presented in a chronological order. The article also mentions the alleged beginnings of the phenomenon of sports tourism dating back to ancient times. The content has been supplemented with the author's remarks. The review of the literature has proved that the phenomenon of sports tourism has not yet been fully described and researched, which is undoubtedly due to the short time of intensification of research and deliberations on this concept.